1993
DOI: 10.1093/schbul/19.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Amino Acid Receptors in Schizophrenia

Abstract: Growing evidence suggests an involvement of excitatory amino acid (EAA) systems in schizophrenia. Precedent exists for changes in binding to kainate, alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid, N-methyl-D-aspartate subtypes of EAA receptors. Current evidence indicates that in schizophrenia, EAA receptor levels can be decreased, unchanged, or even increased in certain brain regions and certain cases. It is likely that variability may arise from different drug histories of patients, other coexisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 64 publications
2
43
0
1
Order By: Relevance
“…In agreement with clinical studies, basic findings indicate that subanesthetic doses of ketamine and other noncompetitive NMDA receptor antagonists produce deficits in acquisition and performance of cognitive tasks, including those that are sensitive to the functional integrity of the PFC (Danysz et al, 1988;Hauber and Schmidt, 1989;Heale and Harley, 1990;Parada-Turska and Turski, 1990;Wesierska et al, 1990;Hauber, 1993;Verma and Moghaddam, 1996). These actions of ketamine are similar to those observed decades ago with phencyclidine (Luby et al, 1959;Davies and Beech, 1960;Bakker and Amini, 1961), which led to the "phencyclidine model of schizophrenia" and, more recently, to several glutamate-and NMDA-related hypotheses of schizophrenia (Kim et al, 1980;Deakin et al, 1989;Wachtel and Turski, 1990;Javitt and Zukin, 1991;Ulas and Cotman, 1993;Olney and Farber, 1995;Akbarian et al, 1996;Coyle, 1996).…”
mentioning
confidence: 81%
“…In agreement with clinical studies, basic findings indicate that subanesthetic doses of ketamine and other noncompetitive NMDA receptor antagonists produce deficits in acquisition and performance of cognitive tasks, including those that are sensitive to the functional integrity of the PFC (Danysz et al, 1988;Hauber and Schmidt, 1989;Heale and Harley, 1990;Parada-Turska and Turski, 1990;Wesierska et al, 1990;Hauber, 1993;Verma and Moghaddam, 1996). These actions of ketamine are similar to those observed decades ago with phencyclidine (Luby et al, 1959;Davies and Beech, 1960;Bakker and Amini, 1961), which led to the "phencyclidine model of schizophrenia" and, more recently, to several glutamate-and NMDA-related hypotheses of schizophrenia (Kim et al, 1980;Deakin et al, 1989;Wachtel and Turski, 1990;Javitt and Zukin, 1991;Ulas and Cotman, 1993;Olney and Farber, 1995;Akbarian et al, 1996;Coyle, 1996).…”
mentioning
confidence: 81%
“…Thus, technical and conceptual issues may be relevant to the failure to replicate findings. Perhaps the variety of disparate hippocampal glutamatergic findings themselves may be important as suggested by Ulas and Cotman, 163 leading to a final common blockade or inhibition of hippocampal efferent pathway activity in schizophrenia.…”
Section: Characteristics Of Postmortem Tissuementioning
confidence: 99%
“…Some magnetic resonance imaging (MRI) studies have found a decrease in prefrontal cortical volume (Harvey et al 1993;Andreasen et al 1994&). Postmortem studies show that schizophrenia patients exhibit alterations in cytoarchitecture of the dorsolateral PFC (Daviss and Lewis 1995;Selemon et al 1995), a loss of glutamate receptor binding (Kerwin et al 1990;Ulas and Cotman 1993), and a decrease in DA fibers in the PFC (Akil and Lewis 1996). From a clinical perspective, many symptoms of schizophrenia resemble those that occur as a result of a lesion in the PFC (Buchanan et al 1994).…”
Section: Cortical Disturbances In Schizophreniamentioning
confidence: 99%